2021
DOI: 10.46328/ijres.1953
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relations between Emotions, Motivation, Classroom Engagement and Achievement in Mathematics

Abstract: The purpose of this correlational research was to examine the relationship between achievement emotions, motivation, and classroom engagement in mathematics among Turkish middle school students, and to determine how these three variables predicted academic achievement in mathematics. 549 seventh grade students in a province located in the south-west region of Turkey participated in the study. Relations among variables were examined by utilizing structural equation modeling.  Results of this study provided evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Also, it was assumed that the findings would give an idea to the education policymakers, curriculum planners, and educators to develop OLS. High self-efficacy increases engagement to target (Bandura, 2010), which increases academic achievement (Alpaslan and Ulubey, 2021;Rodríguez-Muñoz et al, 2021;Tang et al, 2021). Education institutions, especially universities, should attach importance to AS and SEOLE to enhance OLS by conducting studies, which increase awareness for online learning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was assumed that the findings would give an idea to the education policymakers, curriculum planners, and educators to develop OLS. High self-efficacy increases engagement to target (Bandura, 2010), which increases academic achievement (Alpaslan and Ulubey, 2021;Rodríguez-Muñoz et al, 2021;Tang et al, 2021). Education institutions, especially universities, should attach importance to AS and SEOLE to enhance OLS by conducting studies, which increase awareness for online learning.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with medical students, it was found that classroom engagement in applied courses in medical education increased students' academic success (Tengiz et al, 2022). Similarly, studies with middle and high school students have showed that classroom engagement positively predicted students' academic achievement in various subjects (Alpaslan & Ulubey, 2021;Bush et al, 2006;Çelik et al, 2018;Sever et al, 2014). To sum up, students with a higher emotional, behavior and cognitive engagements may have a high achievement score.…”
Section: Classroom Engagement and Academic Achievementmentioning
confidence: 97%
“…Classroom engagement is the process of learning that occurs when EFL learners actively participate in classroom tasks and activities (Alpaslan & Ulubey, 2021). It is the result of active classroom practices that focus on collaborative activities rather than lecture or traditional formats of teaching (Freeman et al, 2014;Menekse et al, 2013).…”
Section: Introductionmentioning
confidence: 99%